A Measurement of Logistics Performance - ARAFAT, AHMAD; SALHA, HASSAN (My University, 2020)
Logistic management within the supply chain network plays a significant role in delivering materials and resources to the construction sites. Logistics operations may be unable to achieve efficient deployment of materials due to several factors such as weak logistical plans, lack of cooperation between different disciplines as well as the congestion of traffic. The term of logistics performance came to analyse the effectiveness and efficiency of logistical tasks such as planning, organizing, coordinating, and controlling the materials flow from the extraction of raw materials to the incorporation into ready-to-deliver end products. Since logistics started gaining valuable importance and becoming more prominent, there is an increasing need to measure the performance of construction logistics. Although several methods investigated the measurements of logistics performance, these methods are still aimed to measure it in the manufacturing industry, and little has shown how that could be implemented in the construction industry. Therefore, this master’s thesis has been directed towards introducing variables that could be used as applicable and straightforward measures for logistics performance. Another intention of this work is to show how the combination of measuring the logistics performance and the practices can lead to optimisations of the logistical plan. In order to achieve the aims of this work, the abductive approach has been followed. The work starts with a literature study on the material flow process and the measures of logistics performance in order to provide preconceptions. Thenceforward, a set of interviews have been carried out to collect the needed data qualitatively. Ultimately, but not last, an estimated case has been generated to show how the logistics performance can be measured according to the proposed framework. In addition, the estimated case has been limited to for prefabricated concrete project since this type of projects is the dominant type nowadays. As expected, the proposed framework is able to measure logistics performance when the needed data are available. Measures such as cost and time have, to an extent, the ability to present the logistics performance. Furthermore, the results displayed that poor logistical plan could lead to cost overrun. On the other hand, various challenges in the construction industry prevent it from achieving a good logistics performance. Therefore, a simple change in the transportation schedule has been conducted in the purpose of optimising the logistical plan. The results of this change exhibited a significant reduction in the logistics cost. Moreover, the interviews showed that several philosophies such as Just-In-Time and Lean should be applied to make the construction industry able to dispose of its logistics poorness.
Keywords: Logistics performance; Performance measurement; Activity-based costing (ABC) theory; Prefabricated concrete flow process; Just-In-Time